2010
DOI: 10.1007/s10484-010-9135-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback Intervention in Fibromyalgia Syndrome; a Randomized, Controlled, Rater Blind Clinical Trial

Abstract: We designed a randomized, rater blind study to assess the efficacy of EEG Biofeedback (Neurofeedback-NFB) in patients with fibromyalgia syndrome (FMS). Eighteen patients received twenty sessions of NFB-sensory motor rhythm (SMR) treatment (NFB group) during 4 weeks, and eighteen patients were given 10 mg per day escitalopram treatment (control group) for 8 weeks. Visual Analog Scales for pain and fatigue, Hamilton and Beck Depression and Anxiety Inventory Scales, Fibromyalgia Impact Questionnaire and Short For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 61 publications
6
101
1
2
Order By: Relevance
“…Very similar therapeutic approaches were used to ameliorate the symptoms of the aforementioned pain disorders. Previously, other researchers described the efficiency of NFB in reducing pain due to headaches, fibromyalgia, and other pain syndromes (Caro & Winter, 2011;Kayiran, Dursun, Ermutlu, Dursun, & Karamürsel, 2007;Kayiran, Dursun, Dursun, Ermutlu, & Karamürsel, 2010;Stokes & Lappin, 2010;Walker, 2011). Stokes reported that 70% of migraine patients experienced at least a 50% reduction in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Very similar therapeutic approaches were used to ameliorate the symptoms of the aforementioned pain disorders. Previously, other researchers described the efficiency of NFB in reducing pain due to headaches, fibromyalgia, and other pain syndromes (Caro & Winter, 2011;Kayiran, Dursun, Ermutlu, Dursun, & Karamürsel, 2007;Kayiran, Dursun, Dursun, Ermutlu, & Karamürsel, 2010;Stokes & Lappin, 2010;Walker, 2011). Stokes reported that 70% of migraine patients experienced at least a 50% reduction in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although feedback can also be based on magnetic (magnetoencephalogram) or on near real-time hemodynamic measures of brain activity (near infrared spectroscopy, real-time functional magnetic resonance imaging) apart from 1 study using tomographic neurofeedback (tNF) [10], only the low cost EEG-based neurofeedback has been used for ADHD treatment. Through operant conditioning, individuals can be trained to control brain electric activity and a growing body of evidence shows that this can be helpful for the treatment of mental/ neurological conditions, such as epilepsy [11], brain injury [12], chronic pain [13], ADHD [14], insomnia [15], and others.…”
mentioning
confidence: 99%
“…(NEUROFEEDBACK BACKGROUND) Neurofeedback (NFT), or computer-aided real-time behavioral training of the electroencephalogram (EEG), has been shown to be a clinically effective treatment for some chronic pain for short periods of time conditions in some situations [4] in peer-reviewed journals. Also, posters/presentations at conferences have been presented on NFTB's effectiveness with pain conditions in certain circumstances [5][6][7][8][9][10][11] and fibromyalgia in particular [12]. However, the use of NFT for chronic neck or back pain beyond the immediate effect to relieve pain does not have any published peer-reviewed research.…”
Section: Introductionmentioning
confidence: 99%